Screening of heavy metal degrading microbes from coal mine soils of Ramagundam and Sathupally - Kondapally Rajani; B. Sreelatha (The Bioscan, 2026)
Bacterial community has been evolving and is been utilized in many ways for human welfare. Their very adaptive nature made them good remediators of the habitat of their presence. Such bacteria presence in the coal mine dumps in particular in the rhizosphere soils are having very vital role. They are the true bioremediation army for the heavy metals present in those soils via various metabolic processes. Such heavy metal degrading microbes are been screened from the rhizosphere soils of Ramagundam and Sathupally coal mine study areas and were studied for their bioremediation property in vitro. It was found that the gram positive bacteria have the capacity of heavy metal bioremediation in a better way than the gram negative ones in the present study. Keywords Bioremediation, heavy metals, bacteria, coal mines, rhizosphere soils